Papillon-Lefevre syndrome: Two case reports - Shah Jigna; Goel Shweta (Wolters Kluwer Medknow Publications, 2007)
Papillon-Lefevre syndrome is a rare autosomal recessive disorder in which there is palmoplantar keratinization and premature loss of both deciduous and permanent teeth. The palmoplantar keratoderma typically has its onset between the ages of 1 and 4 years and severe periodontitis starts at the age of 3 or 4 years. An early diagnosis of the syndrome can help preserve the teeth by early institution of treatment, using a multidisciplinary approach. We present two cases of the syndrome having all of the characteristic features.